Characterization of vibrio cholerae isolated from human Diarrhoea in mymensingh, Bangladesh - Rahamat Ali, Md.; Shahidur Rahman Khan, Md.; Arifa Khatun, Most.; Shah Alam, M.; Mostafa Anower, AKM; Enamul Hoque Kayesh, Mohammad (International Journal of Biological Research, 2014)
Diarrhoeal diseases are one of the top five causes of mortality in all age groups in Bangladesh. An investigation was carried out with the aim of focusing the isolation and characterization of Vibrio cholerae from diarrhoeal stools of human in Mymensingh, Bangladesh. A total of 42 rectal swab samples were aseptically collected from human. Vibrio cholerae was isolated from diarrhoeal stools of human by cultural and biochemical examinations and susceptibility of the isolated Vibrio cholerae to different antibacterial agents was performed by Disc diffusion test. Out of 42 samples, 8 were found to be positive for Vibrio cholerae. The overall prevalence of Vibrio cholerae was 19.05%. The antibiotic sensitivity pattern demonstrated that Vibrio cholerae isolates were highly sensitive to Polymixin B, ciprofloxacin and co-trimoxazole; moderately sensitive to cephalexin and nalidixic acid; less sensitive to erythromycin; and resistant to amoxicillin. This study suggested that there was remarkable prevalence of Vibrio cholerae in human diarrhoea and Polymixin B, ciprofloxacin and co-trimoxazole could be used for treating the patients with diarrhoea caused by Vibrio cholerae. Keywords: Characterization, Vibrio Cholerae, Human, Diarrhoea.